Another Newbie question :)

Hal Daume III hdaume at ISI.EDU
Wed Nov 5 07:17:23 EST 2003

Keith is entirely correct.

> You can see this from the definition of foldr:
> foldr :: (a -> b -> b) -> b -> [a] -> b
> foldr f z   []   = z
> foldr f z (x:xs) = f x (foldr f z xs)
> where clearly every [] is replaced by z and every : by f.

I had heard this before when I was first beginning and didn't really find 
it "clear" :).  I think if you write foldr with f in infix notation it's a 
bit more clear:

> foldr f z       [] = z
> foldr f z   (x:xs) = x `f` foldr f z xs

or even write the second line as

> foldr f z   (x:xs) = x `f` xs'
>   where xs' = foldr f z xs

I think in this case it's a bit more clear how "f" is replacing the ":".

 - Hal

More information about the Haskell-Cafe mailing list